(untitled) (Journal of Educational Sciences, 2020)
Background research is conditioned: firstly, by the importance of processes of modernization of the functioning of market mechanisms of the Kazakh economy, the emergence of new problems of its structural reform and improve competitiveness, especially in the period of post-crisis recovery; secondly, by an innovative social audit nature, relatively recently used in Kazakhstan and has its own national characteristics. This topic assumes special significance in view of the fundamental need for procedures for determining indicators of socio-economic processes; Thirdly, the relevance of gender aspects of social audit. Kazakhstani scientists have been active in the development of social audit in the aspect of regulating social and labor relations. It is advisable to take the following position as the basis for the model of the mechanism of interaction between the systems of state and social-professional assessment of the quality of higher education: representations in the mechanism of the social component by various entities specializing in assessing the quality guarantees of higher education; complementarity of state and public-professional assessment of the quality of higher education based on the mutual interest and correctness of the participants in the educational services market in ensuring the competitive quality of higher education, expanding academic freedoms and autonomy of universities; the need to introduce a mechanism for recognizing and taking into account the results of public and professional assessment of the quality of higher education when deciding on the state accreditation by higher education authorities. Key words: social audit, strategy, development, education reform, educational services, inequality.